Microstructural, Nanomechanical, and Tribological Properties Enhancement of Aluminum Matrix Composite Through High Entropy Alloy Reinforcement - Smith Salifu; Peter Apata Olubambi (Engineering Reports)
ABSTRACT High entropy alloys (HEAs) have gained attention as effective reinforcements for enhancing the properties of metal matrix composites (MMCs), thanks to their distinct properties in contrast to traditional reinforcement particles. In view of that, this study develops HEA‐reinforced aluminum matrix composites (AMCs) consolidated through the pulse electric current sintering (PECS) technique and examines how the HEA reinforcement influences the microstructural, tribological, and nanomechanical properties of these consolidated composites. Appropriate thermodynamic and phase identification equations were used to determine a suitable combination of elements for the development of the HEA reinforcement, and an optimized sintering process was used to achieve effective bonding within the matrix. The resulting composites exhibited enhanced densification, with Laves phase, BCC, and FCC HEA phases present. Furthermore, incorporating HEA reinforcement greatly improved the mechanical properties such as wear resistance, microhardness, and nanoindentation characteristics of the composites such that the composite with 10% HEA displayed about a 191% increase in microhardness, with a significantly lower average coefficient of friction (ACOF) and higher wear resistance as compared to the unreinforced aluminum matrix.